Evaluation of osteoporosis and related factors and quality of life of patients with juvenile idiopathic arthritis and burnout status of parents : Osteoporosis, quality of life and burnout syndrome in juvenile idiopathic arthritis - Yücel, Aylin; Aydog, Ozlem; Karadavut, Kıymet Ikbal; Uneri, Sukran Ozden (Journal of Surgery and Medicine, 2023)
Background/Aim: Juvenile idiopathic arthritis (JIA) can negatively influence the lives of children and parents. Because it is a chronic disease, a complete recovery is not expected; additionally, children with JIA and their parents must cope with problems such as chronic pain, physical disability, school absenteeism, and social communication disorders. Children’s quality of life (QoL) may be affected by all these problems. Also, prolonged exposure to stress and failure to cope with stress may cause burnout syndrome in parents. The study aims to evaluate osteoporosis, QoL of children with JIA and the burnout status of caregivers. Methods: In this prospective, cross-sectional study, 30 patients aged 4–18 years, who were followed up for at least 6 months with the diagnosis of JIA, were included. Demographic, clinical, and laboratory characteristics were recorded retrospectively. Daily dietary calcium intake and daily activity levels were questioned. The patients’ bone mineral densities (BMD) were measured by the Dual Energy X-ray Absorptiometry method. Z scores below -2 were classified as the osteoporosis group, and those above -2 were classified as the non-osteoporosis group. The Turkish Pediatric Quality of Life Inventory validated and reliable in Turkish children was used to evaluate the QoL. Maslach Burnout Inventory was used to evaluate the burnout status of parents. Results: The mean age of patients was 12.6 (4.3) years. Osteoporosis was detected in 46.7% (n=14) cases. The mean age was higher (14.5 [3.7] in the osteoporosis group and 10.9 [4.1] in the non-osteoporosis group) (P=0.032) and the rate of oligoarticular JIA (7.1%), daily calcium intake (288 [168-456] mg/kg), and duration of activity (3 [2-6] hours) were lower in the osteoporosis group (P=0.039, P=0.043, P<0.001, respectively). Among the QoL indicators, the physical health total score was the lowest. Emotional functionality scores decreased as the age increased (P=0.037) and increased as the BMD z-score increased (P=0.024). Emotional burnout, one of the parental burnout indicators, increased as the duration of illness increased (P=0.003), and the BMD z-score decreased (P=0.003). Depersonalization increased as the age increased (P=0.010) and the duration of the disease prolonged (P<0.001) and increased as daily activity duration (P=0.032) and BMD z-score values decreased (P=0.002). Personal achievement decreased as the age increased (P=0.025) and the duration of illness (P=0.014), and the time spent watching television increased (P=0.030). Emotional exhaustion and depersonalization of the parents increased as the scores in any of the indicators of QoL decreased (P<0.05 for each). The personal success of the parents increased as the scores in any of the indicators of QoL increased (P<0.05 for each). All QoL indicators, except for social functionality and psychosocial health total score, were significantly lower in the group with osteoporosis. In addition, parents of children with osteoporosis had higher emotional burnout and depersonalization scores and lowered personal achievement scores (P<0.05 for each). Conclusion: In the current study, we observed a decrease in the QoL of the children and burnout syndrome in the parents. It was found that the deterioration in children’s QoL indicators affected the burnout indicators of parents, and the presence of osteoporosis affected both QoL and parental burnout. Awareness of modifiable risk factors in children with JIA is very important. The disease and osteoporosis secondary to this disease can impair children's QoL and cause burnout in parents.